The decision to work by married immigrant women: the role of extended family households - Heather Antecol; Kelly Bedard (Claremont McKenna College, Department of Economics, 2002)
We find differential rates of cohabitation with adult relatives as well as differential impacts of that cohabitation on the probability of employment for married female immigrants across regions of origin. This suggests that traditions and/or cultural determinants of family structure influence female labor force participation. Not surprisingly, we also find that the labor supply response is biggest for immigrants with young children. This further suggests that cohabitation allows married immigrant women to share childcare and other household responsibilities, which in turn increases the probability that they work outside of the home.
Keywords: J1; 330; Family Structure; Female Labor Force Participation and Immigrants; Frauen; Arbeitsangebot; Frauenerwerbstätigkeit; USA; Migranten; Ehe